Relevansi Nilai-Nilai Pendidikan Perenialisme dalam Penguatan Karakter Peserta Didik pada Era Pembelajaran Digital - Jihan Ulayya; Dimas Seno Aji; Kartika Setiati; Muhlisin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The digital age presents serious challenges for the world of education, particularly regarding the character development of students, which is threatened by a culture of instant gratification, a rapid flow of information, and a potential crisis in moral values. This study aims to analyze the relevance of perennialist educational values as a stable philosophical foundation for strengthening students’ character amid the rapid pace of digital learning. Using the Systematic Literature Review (SLR) method with a descriptive-critical qualitative approach, this study systematically analyzed 21 selected academic sources from Google Scholar and SINTA (2021–2026). The findings indicate that the implementation of Perennialism can be realized through five key strategies: (1) the challenges of education in the digital age, (2) the objectives and urgency of Perennialism, (3) 21st-century learning strategies, (4) character development based on the great books, and (5) the role of teachers as role models. These findings affirm that perennialism is not the antithesis of technological progress, but rather a moral compass that guides the wise and responsible use of technology, thereby fostering a generation that is not only technically competent but also intellectually mature and of noble character.